Prevalence of gizzard erosion among commercial layer chicks in the mining area of Karnataka - MUNIYELLAPPA, H K; GIRIDHARA, P; SATYANARAYANA, M L; GOWDA, N K S (The Indian Journal of Animal Sciences, 2014)
An epidemiological study was conducted to determine the prevalence of various disease conditions among commercial layer flocks in the mining area of northern Karnataka. Flocks — 3 younger and 9 adult— showing poor performance were chosen from 6 different multiage commercial layer farms in the mining area for the study. Flock details including, breed, age, clinical history, mortality pattern, body weights and egg production were systematically recorded. In addition, ND-HI titers, IBD and IBV ELISA antibody titers and trace elements (iron, manganese, lead and cadmium) concentrations in feed, water and tissue samples, gross and microscopic lesions were studied. The study revealed gizzard erosion with cumulative mortality of 8.72, 8.3 and 16.83% in 3 flocks aged 2, 4 and 5 weeks, respectively. Anorexia, uneven growth, dullness, 26.83–48.19% lower body weights, droopy wings, ruffled feathers, pasty vents and penguin posture were the predominant clinical signs observed. Feed samples revealed Fe, Mn, Pb and Cd at 1,100–1,200, 240–340, 4.8–5.2 and 0.0–0.16 ppm, respectively; however water samples did not reveal any abnormality. The liver, kidney and gizzard tissues had higher levels of Fe, Mn, Pb and Cd. The study indicated that exposure to higher levels of Fe and Pb trace elements induced oxyradical cell injury leading to immunosuppression and gizzard erosion.